Preferential query answering in the semantic web with possibilistic networks - Borgwardt, S; Fazzinga, B; Lukasiewicz, T; Shrivastava, A; Tifrea-Marciuska, O (Springer, Cham, 2016)
In this paper, we explore how ontological knowledge expressed via existential rules can be combined with possibilistic networks (i) to represent qualitative preferences along with domain knowledge, and (ii) to realize preference-based answering of conjunctive queries (CQs). We call these combinations ontological possibilistic networks (OP-nets). We define skyline and k-rank answers to CQs under preferences and provide complexity (including data tractability) results for deciding consistency and CQ skyline membership for OP-nets. We show that our formalism has a lower complexity than a similar existing formalism.